FAMA meets MAMA: Revisiting market efficiency through adaptive moving averages - Nor, Safwan Mohd; Aziz, Mukhriz Izraf Azman; Kalyebara , Baliira (International Journal of Accounting, Finance and Business, 2025)
This paper examines the recent performance of the MESA adaptive moving average (MAMA) and following adaptive moving average (FAMA) in the Saudi MSCI Tadawul 30 (MT30) from 2011 to 2025, relative to the buy-and-hold benchmark. Using Sharpe and Sortino ratios, maximum drawdown, Ulcer index, payoff and tail ratios, we assess strategy outcomes across four distinct subperiods reflecting stability, the oil price collapse, reform-driven consolidation and the pandemic era. Results show that buy-and-hold dominates in tranquil and reform-led markets, while MAMA–FAMA provides superior risk-adjusted performance and tail resilience during systemic stress. These findings support the adaptive market hypothesis by demonstrating that efficiency is regime-dependent and evolves with market conditions, underscoring the importance of adaptive strategies in emerging markets.